Corrosion and Materials Selection : a Guide for the Chemical and Petroleum Industries. - Bahadori, Alireza (Wiley, 2014)
This book provides a minimum requirement for consideration when designing systems in order to prevent or control corrosion damage economically and safely in petroleum and chemical industries. It considers various forms of corrosion and prevention methods, including the control of corrosive environments by inhibitors and the monitoring of internal corrosion. Included in the scope are:Corrosion problems in the oil, gas and chemical industries; Corrosion Monitoring including use of corrosion monitoring.